2023
DOI: 10.1007/s10995-023-03860-9
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ Experiences During the 2022 Infant Formula Shortage in Washington D.C.

Allison C. Sylvetsky,
Sarah A. Hughes,
Janae T. Kuttamperoor
et al.

Abstract: Introduction An unprecedented shortage of infant formula occurred in the United States (U.S.) in 2022 and posed widespread challenges to infant feeding nationwide. The purpose of this study is to investigate mothers’ experiences during the 2022 infant formula shortage and its perceived impacts on infants’ diet and health. Methods Mothers (n = 45) of infants under 8 months old from Washington D.C. were invited to participate in a virtual study meeting durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 29 publications
2
1
0
Order By: Relevance
“…The mean helpfulness scores for these resources were moderate with social media scoring the highest. This is consistent with findings from other studies that highlight social media as a powerful tool for diet and health education and support [ 16 , 20 ]. Parents’ mean helpfulness scores for future activities that would facilitate feeding infants in the “near future” included freedom to choose infant formula brands, health insurance coverage for infant formula, online resources describing formula types or brands that meet infants’ unique health needs and free universal prenatal lactation education and postpartum lactation support.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The mean helpfulness scores for these resources were moderate with social media scoring the highest. This is consistent with findings from other studies that highlight social media as a powerful tool for diet and health education and support [ 16 , 20 ]. Parents’ mean helpfulness scores for future activities that would facilitate feeding infants in the “near future” included freedom to choose infant formula brands, health insurance coverage for infant formula, online resources describing formula types or brands that meet infants’ unique health needs and free universal prenatal lactation education and postpartum lactation support.…”
Section: Discussionsupporting
confidence: 93%
“…The unexpected increased use of formula during the shortage in this sample may be explained in part by the use of Operation Fly, increased purchases of infant formula via social media and increased shipments of formula sent from family and friends in the United States. Our observations are consistent with a recent qualitative study that reported white female parents expressed positive feelings for having supportive family members and friends who assisted them to find formula which was not described by any Black or SNAP- or WIC-eligible participants [ 20 ]. Another explanation for the increased use of infant formula during the shortage may be the relatively high rate of stockpiling.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation